2004
DOI: 10.1074/jbc.m407461200
|View full text |Cite
|
Sign up to set email alerts
|

Statin Induction of Liver Fatty Acid-Binding Protein (L-FABP) Gene Expression Is Peroxisome Proliferator-activated Receptor-α-dependent

Abstract: Statins are drugs widely used in humans to treat hypercholesterolemia. Statins act by inhibiting cholesterol synthesis resulting in the activation of the transcription factor sterol-responsive element-binding protein-2 that controls the expression of genes involved in cholesterol homeostasis. Statin therapy also decreases plasma triglyceride and non-esterified fatty acid levels, but the mechanism behind this effect remains more elusive. Liver fatty acid-binding protein (L-FABP) plays a role in the influx of lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
63
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(66 citation statements)
references
References 54 publications
2
63
0
1
Order By: Relevance
“…PPAR-␣ agonists were recently shown to stimulate Mdr2 overexpression, 44 suggesting that this finding could rather be related to the PPAR-␣-activating capacity of atorvastatin. 22 Because an imbalance in the biliary phospholipid and bile acid ratio in Mdr2 knockout mice leads to a cholestatic phenotype resembling primary sclerosing cholangitis, 15,17 it is attractive to speculate that induction of Mdr2 and biliary phospholipid secretion by statins might protect bile ducts against toxic bile acids. [11][12][13] In addition, Asbt was only induced by atorvastatin, which-analogous to human ASBT-could be related to PPAR-␣ stimulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PPAR-␣ agonists were recently shown to stimulate Mdr2 overexpression, 44 suggesting that this finding could rather be related to the PPAR-␣-activating capacity of atorvastatin. 22 Because an imbalance in the biliary phospholipid and bile acid ratio in Mdr2 knockout mice leads to a cholestatic phenotype resembling primary sclerosing cholangitis, 15,17 it is attractive to speculate that induction of Mdr2 and biliary phospholipid secretion by statins might protect bile ducts against toxic bile acids. [11][12][13] In addition, Asbt was only induced by atorvastatin, which-analogous to human ASBT-could be related to PPAR-␣ stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…4B). Because statins were reported to activate peroxisome proliferator-activated receptor ␣ (PPAR-␣), 22 we also determined mRNA levels of the classical PPAR-␣ target gene acyl-coenzyme A oxidase-1. Only atorvastatin was able to significantly induce acyl-coenzyme A oxidase-1 (1.9-fold), while treatment with PB, TCPOBOP, and PCN did not show any induction (data not shown).…”
Section: Effects Of Car and Pxr Ligands On Hepatobiliary Transportmentioning
confidence: 99%
“…31,42 Moreover, statins have been shown to stimulate biliary excretion of phospholipids 34,35 that may further protect bile ducts from immunomediated injury in PBC. 43,44 This may be explained by activation of the nuclear peroxisome proliferator-activated receptor-␣, 45 which is predicted to modulate biliary bile acid/phospholipid ratio via increased biliary phospholipid secretion and increased cholangiocellular reabsorption of biliary bile acids, 31,46 resulting in less aggressive bile.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to their effect on plasma lipid concentrations, statins exert such pleiotropic activities as anti-platelet, anti-oxidant, anti-inflammatory and immunomodulatory activity (Fehrana et al, 2009;Liu et al, 2009). Cross-talk between statins and PPARa was first demonstrated by Martin et al (2001) in human HepG2 hepatoma cells, and subsequent studies showed that statins increase PPARa mRNA levels (Landrier et al, 2004;Sanguino et al, 2005).…”
Section: Discussionmentioning
confidence: 99%